Anti-inflammatory Mechanisms Triggered by Apoptotic Cells during Their Clearance - Szondy, Zsuzsa; Sarang, Zsolt; Kiss, Beáta; Garabuczi, Éva; Köröskényi, Krisztina (Frontiers in Immunology, 2017)
In healthy individuals billions of cells die by apoptosis every day. Clearance of apoptotic cells by phagocytosis (a process called efferocytosis) is very efficient to prevent secondary necrosis and the consequent release of pro-inflammatory cell content that damages the tissue environment and provokes autoimmunity. In addition, apoptotic cells generally induce an anti-inflammatory response, thus removal of apoptotic cells is usually immunologically silent. Since the first discovery that uptake of apoptotic cells leads to transforming growth factor (TGF)-and interleukin (IL)-10 release by engulfing macrophages, numerous anti-inflammatory mechanisms triggered by apoptotic cells have been discovered including release of anti-inflammatory molecules from the apoptotic cells, triggering immediate anti-inflammatory signaling pathways by apoptotic cell surface molecules via phagocyte receptors, activating phagocyte lipid sensing nuclear receptors following uptake and inducing the production of anti-inflammatory soluble mediators by phagocytes that may act in a paracrine or autocrine fashion to amplify and sustain the anti-inflammatory response. Here we summarize our present knowledge about how these anti-inflammatory mechanisms operate during the clearance of apoptotic cells.